2019
DOI: 10.1073/pnas.1817815116
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MAGT1 lead to a glycosylation disorder with a variable phenotype

Abstract: Congenital disorders of glycosylation (CDG) are a group of rare metabolic diseases, due to impaired protein and lipid glycosylation. We identified two patients with defective serum transferrin glycosylation and mutations in the MAGT1 gene. These patients present with a phenotype that is mainly characterized by intellectual and developmental disability. MAGT1 has been described to be a subunit of the oligosaccharyltransferase (OST) complex and more specifically of the STT3B complex. However, it was also claimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 29 publications
5
92
0
Order By: Relevance
“…Because of the broader scope of the clinical findings, we sought additional pathogenetic mechanisms besides the alteration of Mg 2+ transport. Our bioinformatics analysis and other data showed that MAGT1 is the human homolog of the yeast OST3/6 subunit of the OST complex and functions in NLG (15,16,19,22). The recently reported structure of the yeast OST complex showed an integral association of 2 TM helices of OST3 with TM segments of the major catalytic STT3 subunit (32) ( Figure 5A).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Because of the broader scope of the clinical findings, we sought additional pathogenetic mechanisms besides the alteration of Mg 2+ transport. Our bioinformatics analysis and other data showed that MAGT1 is the human homolog of the yeast OST3/6 subunit of the OST complex and functions in NLG (15,16,19,22). The recently reported structure of the yeast OST complex showed an integral association of 2 TM helices of OST3 with TM segments of the major catalytic STT3 subunit (32) ( Figure 5A).…”
Section: Resultssupporting
confidence: 54%
“…Our glycoproteomics analysis also revealed that defective glycosylation in XMEN disease preferentially affects NxS sequons. We found that most affected glycosites were located within 60 show that sTfs from patients with XMEN also have a mild defect in final processing of the glycans (22). Furthermore, and in contrast with most CDG type I in which Apo-CIII is not affected, patients with XMEN may also have an OLG defect in Apo-CIII, which could be secondary to defective NLG of components of the OLG enzymatic apparatus.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this setting, one can speculate that the defect in NKG2D N‐glycosylation (which might depend on Mg ++ ) increases NKG2D degradation by the ubiquitin‐proteasome pathway and thus leads to an impairment in NKG2D expression. This hypothesis is supported by the observation of an N ‐glycosylation defect in three recently described new patients with MAGT1 deficiency . Intriguingly, two of these patients had developmental delay but no signs of immunodeficiency ‐ possibly because they have not yet encountered EBV.…”
Section: Immunodeficiencies Causing Ebv‐driven B‐lymphoproliferative mentioning
confidence: 67%
“…The expression of CD70 can be induced on a variety of immune cells, including dendritic cells and activated B and T cells . However, CD70 is not expressed on human peripheral blood mononuclear cells ‐ with the exception of a small subset of B cells . CD70 is also strongly expressed by B‐cell lymphomas and other cancers, such as carcinomas .…”
Section: Immunodeficiencies Causing Ebv‐driven B‐lymphoproliferative mentioning
confidence: 99%